2015
DOI: 10.1016/j.ccell.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A LIN28B-RAN-AURKA Signaling Network Promotes Neuroblastoma Tumorigenesis

Abstract: SUMMARY A more complete understanding of aberrant oncogenic signaling in neuroblastoma, a malignancy of the developing sympathetic nervous system, is paramount to improving patient outcomes. Recently, we identified LIN28B as an oncogenic driver in high-risk neuroblastoma. Here, we identify the oncogene RAN as a LIN28B target and show regional gain of chromosome 12q24 as an additional somatic alteration resulting in increased RAN expression. We show that LIN28B influences RAN expression by promoting RAN Binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 66 publications
1
94
0
Order By: Relevance
“…Recently, LIN28B was identified as an oncogenic driver in high‐risk neuroblastoma 30. LIN28B–RAN–AURKA signaling was further revealed to drive neuroblastoma oncogenesis 19. We were interested in determining whether LIN28, RAN, and AURKA act as oncogenes in hepatoblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, LIN28B was identified as an oncogenic driver in high‐risk neuroblastoma 30. LIN28B–RAN–AURKA signaling was further revealed to drive neuroblastoma oncogenesis 19. We were interested in determining whether LIN28, RAN, and AURKA act as oncogenes in hepatoblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, LIN28A plays a functional role in the maintenance of the ALDH1-positive CSC population in tumors35. LIN28B also influences multiple oncogenic signaling networks in diverse cellular contexts, and is being recognized as oncogenic stem-cell factor2736. Indeed, CD166-positive tumor-initiating cells obtained from primary NSCLC tumor expressed high levels of LIN28B27.…”
Section: Discussionmentioning
confidence: 99%
“…In p53-deficient and p53-mutant cells, these regulatory mechanisms are disrupted, and Aurora-A expression and stability are elevated. Functional genomic studies in N-Myc-amplified neuroblastoma have revealed that LIN28B RNA-binding protein promotes RAN level by directly binding to RAN mRNA and via RANBP2 by inhibiting let-7 expression, consequently facilitating Aurora-A activation and stabilization which in turn promote N-Myc stabilization (44). It was recently been reported that Aurora-A acts as a transactivating factor for hnRNPK, a known transcriptional cofactor of p53, to promote c-Myc expression and reciprocal c-Myc-mediated transactivation of Aurora-A gene in breast cancer stem-like cells (46).…”
Section: Mechanism Of Downregulation Of Aurora Kinases By P53mentioning
confidence: 99%